Starch Phosphate Production by Microwave Technique - Maneesriraj, Passara; Phetkoa, Siriluk; Narkrugsa, Woatthichai (Agriculture and Natural Resources, 1998)
Starch phosphate production using microwave technique was carried out with tapioca and glutinous rice starches as raw materials. Starches were mixed with phosphate reagents(sodium hexametaphosphate and sodium dihydrogen-phosphate to produce starch phosphate monoester (SPM) and starch phosphate diester (SPD) at the concentration of 10,15 and 20% ( w/v in liquid phase) with the liquid/solid weight ratio 1:2. Retained moisture content(RM),bound phosphorus (BP), degree of substitution (DS) and freeze-thaw stability (FTS) of starch phosphates were analysed and examined. The results showed that RM of SPM from tapioca and glutinous rice starch were 6.47-9.28% and 6.24-8.08%,respectively, while RM of SPD from the two starches were 5.70-9.24% and 5.35-8.08%,respectively. Starch phosphate from tapioca starch had BP (0.062-0.085% in SPM and 0.052- 0.072% in SPD)lower than starch phosphate from glutinous rice starch(0.091-0.147% in SPM and 0.074-0.131% in SPD). DS of starch phosphates from tapioca starch(0.0045-0.0068 for SPM and 0.0037-0.0053 for SPD) were also lower than from glutinous rice starch (0.0053-0.0104 for SPM and 0.0047-0.0092 for SPD). FTS of SPM and SPD from glutinous rice starch were better than FTS of SPM and SPD from tapioca starch because of lower volume of seperated water after freezing and thawing. BP and DS were almost significantly positive correlated to the interaction of factors between the concentration of phosphate reagent and heating time at P≤0.05. Starch phosphate from glutinous rice starch, especially in the monoester form was more suitable to use in frozen food than tapioca starch.